Processing of Functional Yoghurt-Like Product from Soymilk Supplemented by Probiotics - Enas Almghawesh; Samir Slik; Hussam Okkou (International Journal of Food Science)
In this study, a new functional yoghurt-like product was manufactured using soymilk (sample B), mix of soymilk and cow milk (sample C), and both were compared with yoghurt of cow milk (sample A) as a control. The three yoghurt samples (A, B, and C) were processed using the traditional starter culture and Bifidobacterium bifidum: (A) 100% cow milk yoghurt, (B) 100% soymilk yoghurt, and (C) (50%cow milk+50%soy milk) yoghurt. All samples were stored at 4°C for 15 days and analyzed on 1st, 7th, and 15th day of the storage period. The results showed that all samples have kept a vital force of 106 colony/g until the 15th day of cooled storage period, and thus, achieving the feature of probiotic food. Moreover, soymilk yoghurt had the highest content of protein (3.75%) and the highest levels of unsaturated fatty acids, making it nutritious and healthy food. Furthermore, it had an acceptable taste, smell, and a firm texture. This product may be considered as a probiotic vegan and partial alternative to cow milk yoghurt. Additionally, adding probiotic bacteria prolonged the shelf-life and improved the flavor of soymilk.